Iron-Decorated Nitrogen/Boron co-Doped Reduced Graphene Oxide Aerogel for Neutral Rechargeable Zn-Air Batteries - Yuyun Irmawati; Falihah Balqis; Pilar Bela Persada; Fredina Destyorini; Rike Yudianti; Ferry Iskandar; Afriyanti Sumboja (Batteries, 2023)
Zn-air batteries (ZABs) with neutral electrolytes offer a significantly longer lifespan and better recyclability than alkaline ones. However, low-performance bifunctional catalytic activities for oxygen reduction or evolution reaction (i.e., ORR/OER) in neutral electrolytes still hamper their development. Here, we report iron nanoparticle-decorated nitrogen/boron co-doped reduced graphene oxide aerogel (Fe-NBrGO) with distinguished ORR/OER activity, enabling its application in neutral rechargeable ZABs. Taking advantage of the formation of 3D porous structure of graphene aerogel, N/B-moieties active sites, and Fe-containing active sites, Fe-NBrGO exhibits high ORR onset potential (1.074 and 0.817 V) and adequate OER overpotential (476 and 615 mV) in alkaline and neutral electrolytes, respectively. Fe-NBrGO enables the production of a neutral-ZAB with 34 mW cm−2 in peak power density and remains stable for a 284 h (~852 cycles) cycling test. This research highlights the rational design of highly active oxygen catalysts for the widespread implementation of new energy storage technologies.